Pemanfaatan Youtube Dalam Mendukung Persiapan Olimpiade IPA Jenjang SMP - Aji Saputra; Ismi Musdalifah Darsan; Saprudin Saprudin; Fatma Hamid; Nurdin Abdul Rahman; Dewi Amiroh; Sitti Mukarramah; Syahrial Maulana; Zandy Pratama Zain; Nurul Ainun Tangge; Nasrun Balulu; Usman Sambiri; Nur Fajrhi; Hutri Handayani Isra; Iqbal Limatahu; Chumidach Roini; Sumarni Sahjat; Krishna Aji; Andy Hermawan (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community service aims to provide learning videos to all participants in the National Science Olympiad in Natural Sciences. This learning video is a free learning resource that can be accessed anytime and anywhere via the YouTube platform. These learning videos consist of 9 videos containing OSN Science grids and are collected into one playlist entitled KSN IPA (Fisika) SMP. The use of YouTube in supporting preparations for the science olympiads at junior high school level can be said to be effective by looking at the number of viewers, the number of likes and that no one gave a dislike. Ease of access and targeted material content can be something that attracts students participating in OSN. Even the comments column can also be used as a medium for discussion and correction of each material presented.